Intratumor morphologic and molecular genetic heterogeneity in astrocytomas of different grade of malignancy in the material from the first operation - D. E. Matsko; M. V. Matsko; A. O. Baksheeva; E. N. Imyanitov; A. Yu. Ulitin; V. M. Moiseenko; K. V. Shelekhova; N. M. Volkov; A. G. Ievleva; V. I. Tiurin; S. S. Sklyar; A. A. Zrelov; et al. (Сибирский онкологический журнал, 2022)
Introduction. Intratumor heterogeneity is one of the key reasons for unfavourable prognosis in malignant tumors. Astrocytic tumors are known to develop therapy resistance inevitably during the course of disease. One of possible reason is tumor heterogeneity. Purpose. The aim of this work was to assess the intratumor morphologic and molecular heterogeneity in diffuse astrocytoma, anaplastic astrocytomas and primary glioblastomas. Material and methods. We conducted morphologic (n=22) and molecular-genetic (n=8) analysis of surgical specimens obtained from primarily operated glioblastoma giv (gb), anaplastic astrocytomas giii (aa) and diffuse astrocytoma gii (da) patients aged 18 years and older in whom total or subtotal tumor resection was performed. Tissue sampling for the analysis was performed from 5 equidistant areas of each tumor. Morphologic diagnosis was established according to who classification of central nervous system tumors (2007/2016). Mgmt, c-kit, top2a, pdgfr-α, ercc1, vegf genes mrnaexpression was assessed by rt-pcr. Idh1 and idh2 mutational status was evaluated by allele-specific pcr. Results. Morphologic heterogeneity was evident in 72,7 % tumors (16/22) overall. Heterogeneity was observed in 68,8 % (11/16) of gb, 80 % (4/5) of aa and in the only case of da. In 50 % of cases at least 3 different morphologic variants were seen in different areas of the tumor. This morphologic heterogeneity presented as the combination of different grades of anaplasia (gii – giv) in one tumor. Molecular profile was assessed in 48 expression analysis of genes: mgmt, c-kit, top2a, pdgfr-α, ercc1, vegf from 8 patients. Intratumoral molecular heterogeneity was revealed in 41,7 % of cases (20/48). Conclusion. The presence of intratumoral heterogeneity should be taken into account during surgery for adequate tumor sampling for histologic and molecular analysis which is critical for proper assessment of prognosis and following treatment planning.